Seleção e utilização de bactérias amilolíticas para a produção de sorvete de inhame (Dioscorea sp) - Batista, Nádia Nara (2018)
The lactic acid bacteria (LAB) are commonly used as starter culture in fermentative process because in addition their probiotic properties they can ferment different substrates. Researches and developments of new plantbased foods have increased in recent years due the growing demand of nondairy industrialized foods that contribute to consumer health and well-being. However, the main challenge of these products is the acceptability of the final product. The aim of the study was to select amylolitic lactic acid bacteria producing phytase and to evaluate their behavior during yam fermentation. In addition, non-dairy fermented foods with reduced fat concentration was developed and characterized, and its acceptability by consumers was also evaluated. Thirteen strains of BAL were previously selected for amylase production. Among these strains, Leu. lactis CCMA 0415, Lb. plantarum CCMA 0744 and Lb. fermentum CCMA 0745, were selected due their ability to produce phytase, reduce the pH (from 6.0 to around 3.8) and grow (reaching around 8 log UFC/mL) during 24h of fermentation. Among them, Leu. lactis CCMA 0415 was selected for next studies because its ability to keep viability above 8 log UFC/mL and did not reduce diosgenin concentration (8.0 µg/mL) after 24h of yam fermentation. A non-dairy with reduced fat ice cream was prepared from fermented and non-fermented yams. The fermentation was conducted by selected Leu. lactis, which remained viable (10 7 CFU/g) for 90 days of storage. The fermentative process reduced the concentration of starch (from 26.82 to 22.35%) and protein (from 4.68 to 3.99%), and increased some minerals concentration probably due to the reduction in phytate concentration. The total phenolics concentration for the fermented and non-fermented ice cream was 51 and 54 mg, respectively, and the radical scavenging activity was 18 and 10% by the DPPH methods and 44 and 26% by the ABTS methods, respectively. The ice cream was characterized as non-Newtonian fluid and exhibiting pseudoplastic behavior (n <1). Low value of melting (0.5 g/min) and high value of overrun (>200%) were obtained for ice cream. Sensorial analysis was performed by acceptance and CATA tests evaluated in two sessions. In the acceptance test, the flavor attribute showed a significant difference (p <0.05) between the two sessions. The ice cream description was obtained by CATA test and the results were analyzed by principal component analyses (PCA) which showed two distinctive group, one for first session and other for the second session. The first session was characterized by coconut water and acid flavor and sandy texture, while the second session the perception was yogurt flavor and creamy texture. Therefore, Leu. lactis CCMA 0415 is a promising strain to be used as starter culture in yam fermentative processes. The fermented yam showed to be a good substitute for milk to produce ice cream with reduced fat contend.